Geophysical Characterization of São José do Vale do Rio Preto to Identify Uranium Occurrences in Groundwater, Southeast of Brazil - JUAREZ LOURENÇO; FELIPE FRAIFELD; NICOLAS R. HISPAGNOL; GIOVANNI C. STAEL (Anais da Academia Brasileira de Ciências, 2025)
Abstract The deterioration of surface water quality in the hydrographic basins of the mountainous region of Rio de Janeiro, Brazil, has led to an increasing dependence on well drilling for access to groundwater. Although this groundwater is often considered a high-quality source suitable for consumption, it may contain elevated concentrations of Uranium (U) due to the regional lithological geochemistry. The study area, located in São José do Vale do Rio Preto (Rio de Janeiro, Brazil), features a complex geological composition that influences the hydrochemical in the region’s fractured aquifers. This research primarily aimed to investigate the factors contributing to high levels of U in groundwater in this region. Advanced geophysical techniques were employed, including gamma-ray spectrometry to assess radioelement concentrations and magnetometry to map structural directions in the area. The study mapped contamination patterns both on the surface and subsurface, establishing a precise correlation between groundwater flow dynamics and the influence of the Central Tectonic Boundary (CTB), a significant transpressive shear zone affecting the regional geological structure. In addition to the geophysical data analysis, the research evaluated the impact of local geological formations on U distribution in well samples. By integrating these results, the study clarified the relationship between geological formations, groundwater flow, and U contamination. This understanding can guide strategies to mitigate water quality issues and provide insights for more effective groundwater management practices in the region.